1984
DOI: 10.1246/bcsj.57.3339
|View full text |Cite
|
Sign up to set email alerts
|

Preparatively Useful Method for the Synthesis of Diels-Alder Adducts between Furan and Methyl Acrylate

Abstract: The Diels-Alder adducts of furan with methyl acrylate were successfully prepared by two methods on a preparative scale. The BF3·OEt2-catalyzed reaction of furan with methyl acrylate gave a 7:3 mixture of endo and exo adducts in 75.7% yield. When acryloyl chloride was used as a dienophile, after esterification with methanol, a 3:7 mixture of the same adducts was obtained in 76.5% overall yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…-11exen-3-01 (25) Using general procedure 2, iodide 22 (0.51 g, 2.18 mmol) was treated with rert-butyllithium (2.82 mL, 4.79 mmol) and methacrolein (0.27 mL, 3.26 mmol) to produce compound 25 (0. 7-(2-F111yI)-2-lzepte11-4-o/ (26 (E)-7-(2-F~~ryl)-3-t~1c~thj~l-2-hepte1~-4-o/ (27) Using general procedure 2, iodide 22 (1.56 g, 6.63 mmol) was treated with ter-t-butyllithium (8.58 mL, 14.58 rnmol) and tiglic aldehyde (0.96 mL, 9.94 mmol) to produce compound 27 (0.58 g, 3.00 mmol) as a clear, colourless oil in 45% yield after purification by flash chromatography (7: 1) …”
Section: -(2-(5-methylfury1))-1 -Ckloropropane (21)mentioning
confidence: 99%
“…-11exen-3-01 (25) Using general procedure 2, iodide 22 (0.51 g, 2.18 mmol) was treated with rert-butyllithium (2.82 mL, 4.79 mmol) and methacrolein (0.27 mL, 3.26 mmol) to produce compound 25 (0. 7-(2-F111yI)-2-lzepte11-4-o/ (26 (E)-7-(2-F~~ryl)-3-t~1c~thj~l-2-hepte1~-4-o/ (27) Using general procedure 2, iodide 22 (1.56 g, 6.63 mmol) was treated with ter-t-butyllithium (8.58 mL, 14.58 rnmol) and tiglic aldehyde (0.96 mL, 9.94 mmol) to produce compound 27 (0.58 g, 3.00 mmol) as a clear, colourless oil in 45% yield after purification by flash chromatography (7: 1) …”
Section: -(2-(5-methylfury1))-1 -Ckloropropane (21)mentioning
confidence: 99%
“…4, eqn (3)). 21 A year later, Ogawa and co-workers developed an optical resolution of (AE)-7-endooxabicyclo[2.2.1]hept-5-ene-2-carboxylic acid by the use of (R)-(+)-and (S)-(À)-a-methylbenzylamine, respectively. 22 In 1986, Koizumi et al 23 reported the first asymmetric synthesis of 7-oxabicyclo[2.2.1]hept-5-ene-2-carboxylate by means of a highly diastereoselective Diels-Alder reaction employing optically active 3-(2-pyridylsulfinyl)acrylates (S)-24 or (R)-24, respectively.…”
Section: -Carbethoxy-7-oxabicyclo[221]hept-5-enementioning
confidence: 99%
“…However, preparation of this intermediate itself proved to be difficult because, while the Diels-Alder reaction of furan and acrylate derivatives is a powerful means of synthesizing this class of compound, [24,32] no method suitable for the large-scale preparation of the endo isomer has yet been described. Establishing such a route was our first goal.…”
Section: Second-generation Monomer Synthesismentioning
confidence: 99%